Towards resilient and low-emission agriculture: A review of climate change policy instruments for Colombia’s agricultural sector - Rivas, Juan Sebastian; Martinez Baron, Deissy; Castellanos, Andrea (2025)
This report examines the alignment between Colombia’s national climate policy framework and its agricultural commitments under the Nationally Determined Contribution (NDC 2020), with the objective of identifying opportunities to support implementation through scalable innovations. Using a structured content and gap analysis of 30 national policy instruments, the study identifies 101 sectoral goals related to climate adaptation and mitigation in agriculture. The analysis shows that, while Colombia has established a comprehensive regulatory and institutional framework, important gaps persist in operationalization, monitoring, and verification. To explore how these gaps could be addressed, the report maps selected CGIAR innovations against the identified policy and implementation needs, applying a scaling readiness lens to focus on high‑maturity solutions with demonstrated potential for broader uptake. The analysis highlights examples such as digital agroclimatic advisory tools, sustainable livestock models, and low‑carbon rice technologies as relevant options to support the execution of existing climate commitments. The report illustrates how scalable scientific innovations may contribute to bridging the gap between policy ambition and practical action in Colombia’s agrifood systems.